Flow-Induced Vibration Response of the Chenderoh Dam Bottom Outlet Section Due to the Effects of Water Spilling - Ghazali M.H.M.; Mazlan A.Z.A.; Azman M.A.; Zawawi M.H.; Radzi M.R.M. (Institute of Physics Publishing, 2023)
Dams; Disaster prevention; Frequency domain analysis; Natural frequencies; Vibrations (mechanical); Flow induced vibrations; Frequency domain response; Natural frequencies and modes; Operating condition; Operating frequency; Operational deflection shapes; Resonance phenomena; Transient vibration response; Rivers